EVALUASI PENGGUNAAN MEDIA KARTU KATA BERGAMBAR TERHADAP KETERAMPILAN MEMBACA PERMULAAN PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS 1 SD NEGERI 42 BANDA ACEH - Khairunnisa; Teuku Mahmud; Hendra Kasmi (STKIP Subang, 2026)
This study aims to evaluate the use of illustrated word card media in improving beginning reading skills in Indonesian subjects for first-grade students at SD Negeri 42 Banda Aceh. This study uses a qualitative descriptive case study approach integrated with the CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques included observation, interviews, and documentation. The subjects of the study were 34 first-grade students. Context evaluation showed that students initially faced challenges in letter recognition, lower learning motivation, and adaptation issues. Input evaluation indicated that the teacher independently prepared the lesson plans and visual media within 1–2 days. Process evaluation demonstrated structured classroom management through group division based on student abilities, although small focus disruptions occurred. Product evaluation revealed a highly significant positive impact: 22 students (64.70%) achieved the very high ability category, 10 students (29.41%) reached the high category, and only 2 students (5.88%) remained in the low category. Overall, the integration of illustrated word cards effectively bridges the visual and cognitive needs of early childhood readers.